PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KINERJA KEUANGAN, INFLASI, NILAI TUKAR DAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - ratna sari; indah lia puspita; muhammad luthfi; Lestari Wuryanti (Universitas Malahayati, 2022)
This study aims to determine the Investment Decisions, Funding Decisions, Financial Performance, Inflation, Exchange Rates, and Dividends Against Stock Prices. This study uses data from the 2016-2018 Financial Statements. The object of this research is Manufacturing Companies listed on the Indonesia Stock Exchange(IDX).Data collection method used in this study is purposive sampling method, which is the determination of samples based on the suitability of certain characteristics and criteria. Based on the purposive sampling method, obtained research samples were conducted on 105 samples of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2016-2018. Hypothesis testing in this study was carried out by using multiple linear regression analysis methods in the Eviews 8.1 applicationprogramKeywords: Investment Decisions, Funding Decisions, Financial Performance, Inflation, Exchange Rates, Dividends and StockPrices.